The university’s mission and human capital (Journal of Philosophy Culture and Political Science, 2021)
This article analyzes the transformation of the idea of the university, its identity, caused by changes in the landscape of modern higher education. It is noted that the current conditions for the functioning of universities (global information flows, the reform of the higher education system, changing landscape of higher education, and others.) Re-actualize the universities searching for their identity, identify and underline its originality and exclusivity.Key words: higher education, globalization, reform, university, identity.